Issues and challenges of sustainable agriculture in the Cameron Highlands - Barrow, C.J; Ngai Weng, Chan; Tarmiji Masron (Environmental Management Society, Malaysia, 2009)
The challenge of producing enough food is increasingly affecting almost all developing countries as they prioritise support for industry ahead of agriculture. However, in recent decades, many countries, including Malaysia, have realised the need for food security and self-sufficiency and have embarked on an intensive agricultural programme. Consequently, many tropical highlands suitable for crops are suffering environmental damage through intensive farming with little or no enforcement and control. The Cameron Highlands of Malaysia is an example whereby large tracts of pristine montane forests have been cleared for intensive farming, both for food crops and flowers. This paper examines how farmers, with little government help, interact with environment, changing markets, infrastructure development, indigenous peoples, tourism, and other factors. The paper is based on detailed observation and interviews with farmers, grower associations, government officers and indigenous people to gather information related to farming, land degradation, threats to production and possible sustainable farming options. The results show that Cameron Highlands farmers, despite being left alone facing great challenges, are adapting well and are often flourishing. Many have intensified production, and some are moving toward less environmentally-damaging sustainable strategies. Pressure from NGOs and civil society with stricter government regulation has led to better control of land clearance and degradation, but this has forced farmers to move to neighbouring states. Organic farming is taking off though only a small percentage of growers are involved. Overall, the farmers have demonstrated great resilience, learnt new techniques, initiated and supported more environmentally friendly farming methods, and adapted well to environmental and socio-economic change with little or no outside help